An other self? Education, foreignness, reflexive comparison and capability as connection. Issue 1 (2nd January 2020) - Unterhalter, Elaine
ABSTRACT: The article is an attempt to explore through the lens of my identification as a foreigner, a number of different themes around work in comparative education, particularly aspects of the question of method, and some reflections on the relationship with education and international development. The discussion begins with some reflection on internal or external foreignness, and the ways in which these identifications within my autobiography are heterodox, not singular and co-constructed with many relationships, changing over time. Some different formulations of pluralism and engagements with the capability approach are discussed drawing out some of the resources they provide for exploring approaches in comparative education. In the final section, some features of the idea of reflexive comparison as a methodological resource are sketched.